2002
DOI: 10.7589/0090-3558-38.1.228
|View full text |Cite
|
Sign up to set email alerts
|

Notoedric and Sarcoptic Mange in Free-ranging Lynx from Switzerland

Abstract: Between March and December 1999, five free-ranging lynx (Lynx lynx) affected by mange were found dead or shot by game wardens in the Swiss Alps. In the first two cases, Notoedres cati was isolated from the skin; in the third and fourth case, Sarcoptes scabiei was the cause of the infection; and in the fifth case, a mixed infection was diagnosed. Red foxes (Vulpes vulpes) affected with sarcoptic mange and domestic cats infested with N. cati are likely to be the sources of infection. It seems improbable that man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
62
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 12 publications
6
62
0
Order By: Relevance
“…This observation has also been reported in red foxes from other populations (Little et al, 1998;Bornstein et al, 1995Bornstein et al, , 2001, in lynx (Ryser-Degiorgis et al, 2002), in cheetahs (Acinonyx jubatus; Caro et al, 1987), and in humans with crusted scabies (McCarthy et al, 2004). Activated lymph follicles are congruent with the cell-mediated immune response observed with severe mite infestation (Bornstein et al, 2001) and may also be related to secondary infections of the damaged skin.…”
Section: Dermatohistology and Cellular Responsesupporting
confidence: 75%
See 3 more Smart Citations
“…This observation has also been reported in red foxes from other populations (Little et al, 1998;Bornstein et al, 1995Bornstein et al, , 2001, in lynx (Ryser-Degiorgis et al, 2002), in cheetahs (Acinonyx jubatus; Caro et al, 1987), and in humans with crusted scabies (McCarthy et al, 2004). Activated lymph follicles are congruent with the cell-mediated immune response observed with severe mite infestation (Bornstein et al, 2001) and may also be related to secondary infections of the damaged skin.…”
Section: Dermatohistology and Cellular Responsesupporting
confidence: 75%
“…Drastically decreasing fat deposits in association with mite infestation have been described in foxes (Gortá zar et al, 1998;Balestrieri et al, 2006), coyotes (Canis latrans) and wolves (Canis lupus; Todd et al, 1981), lynx (Ryser-Degiorgis et al, 2002), ibex (Leon-Vizcaino et al, 1999), and chamois (Rupicapra rupicapra; Rossi et al, 2007). Newman et al (2002) reported reduced fat reserves together with accelerated muscle catabolism in foxes with severe hyperkeratotic mange and suggested that inappetence increases with severity of infestation.…”
Section: Dermatohistology and Cellular Responsementioning
confidence: 99%
See 2 more Smart Citations
“…Various wildlife species in turn were infected, often from contact with their domestic counterparts (Pence and Ueckermann, 2002). Sarcoptes mite infections are endemic in many European wild mammal populations, causing devastating mortality (up to>90%), reported especially from Alpine and Pyrenean chamois, Iberian ibex, aoudad and red fox, whereas only few cases have been reported in the stone marten, badger and roe deer (Ryser-Degiorgis et al, 2002;Gonzá lez-Candela et al, 2004;Rossi et al, 2007;Oleaga et al, 2008). Apparently, no epidemiological relationship exists, in Europe, between mange foci affecting wild ruminants, wild boars and carnivores.…”
Section: Introductionmentioning
confidence: 99%